2011
DOI: 10.1074/jbc.m111.224857
|View full text |Cite
|
Sign up to set email alerts
|

Endospanins Regulate a Postinternalization Step of the Leptin Receptor Endocytic Pathway

Abstract: Endospanin-1 is a negative regulator of the cell surface expression of leptin receptor (OB-R), and endospanin-2 is a homologue of unknown function. We investigated the mechanism for endospanin-1 action in regulating OB-R cell surface expression. Here we show that endospanin-1 and -2 are small integral membrane proteins that localize in endosomes and the trans-Golgi network. Antibody uptake experiments showed that both endospanins are transported to the plasma membrane and then internalized into early endosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 32 publications
4
49
1
Order By: Relevance
“…Silencing of LEPROT increases leptin receptor localization on the plasma membrane (20,22), whereas overexpression of LEPROT decreases cell-surface exposure of leptin receptor (20) and GH receptor (19). The effect of LEPROT on the intracellular trafficking of membrane receptors appear to be specific, as it has been shown that it does not affect EGF receptor trafficking (19,20,22). LEPROT and LEPROTL1 mRNAs are widely expressed in mammalian tissues and organs, including the liver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Silencing of LEPROT increases leptin receptor localization on the plasma membrane (20,22), whereas overexpression of LEPROT decreases cell-surface exposure of leptin receptor (20) and GH receptor (19). The effect of LEPROT on the intracellular trafficking of membrane receptors appear to be specific, as it has been shown that it does not affect EGF receptor trafficking (19,20,22). LEPROT and LEPROTL1 mRNAs are widely expressed in mammalian tissues and organs, including the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The leptin receptor overlapping transcript (LEPROT, also known as endospanin-1 or obesity receptor gene-related protein, OB-RGRP) belongs to a family of genes that includes two other members: one in mammalian cells (LEPROT-like 1, LEPROTL1, or endospanin-2) (20,24) and another in Saccharomyces cerevisiae (vacuolar protein sorting 55, VPS55) (25). These genes encode small proteins with four potential transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endo1 is a small protein with 4 transmembrane domains, encoded in humans by the same gene as ObRb via alternative splicing, but without amino acid sequence similarity with the receptor [59, 60]. Besides the genetic link, Endo1 and ObRb display similar expression profiles, in particular in the hypothalamus, and are located in similar intracellular compartments (Golgi, trans-Golgi and late endosomes) [61], suggesting a functional interrelationship. We have shown that Endo1 interacts with ObRb, traps the receptor inside the cell and directs it from endosomes to lysosomes for degradation [61] (Fig.…”
Section: Endo1 a Partner Of Obrb Involved In The Control Of Energy Amentioning
confidence: 99%